Method for enhancing composite interface of high polymer material and ceramic coating
Through the composite interface enhancement method between polymer materials and ceramic coatings, the problem of low density and easy fall-off of ceramic coating composite materials is solved, and the high density and multi-performance improvement of ceramic coatings is achieved.
Patent Information
- Application Number
- CN202411256866.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional ceramic coating composite materials have low density and are prone to fall off after coating, which cannot meet the needs of use.
The composite interface enhancement method of polymer materials and ceramic coatings is adopted, including material selection, surface treatment, chemical reaction deposition, multi-layer coating and acid-base neutralization density treatment, and select fiber laying and sandblasting such as alumina fibers. Processing, reactant gas permeation and polymer material coating to form a high density ceramic coating.
It significantly improves the density of the ceramic coating, avoids falling off, enhances bending, compression, wear, corrosion, and high temperature resistance, and meets the needs of use.
Smart Images

Figure CN119116238A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic coating composite materials, in particular to a composite interface reinforcement method of a polymer material and a ceramic coating. Background Art
[0002] Ceramic coating is a general term for a class of inorganic non-metallic coatings, which refers to spray coatings whose coating materials are ceramics. Its composition includes: oxide coatings, non-oxidation coatings, silicate coatings, composite ceramic coatings, and due to the particularity of its materials, ceramic coatings also have the advantages of wear resistance, corrosion resistance, anti-sticking, high hardness, high temperature resistance, and good biocompatibility. Ceramic coatings can flexibly combine the high temperature resistance, wear resistance, and corrosion resistance of ceramic materials with the high strength and toughness, machinability, and electrical and thermal conductivity of metal materials, so as to maximize the comprehensive advantages of the two types of materials and meet the needs of mechanical products for structural performance and environmental performance; there are many types of materials that can be used to prepare ceramic coatings, and ceramics and ceramics, ceramics and metals, ceramics and plastics can be used in combination as needed. And it is easy to combine with the original tooling conditions of metal processing to realize the technological transformation of enterprises; ceramic coatings are easy to form, the deposition rate is fast, and the coating thickness is controllable. Different sintering processes can be used to spray on the surface of thin-walled parts, hollow parts, and special-shaped parts, and local spray strengthening of products can also be achieved; ceramic coatings can be prepared on different substrates with good processing performance. For example, the properties of various metals, cement, refractory materials, stone gypsum and other inorganic materials; plastics and organic materials; wood, cardboard, etc. can be improved by spraying ceramic coatings. After the ceramic coating is damaged, the metal substrate can be reused (the same is true for other substrates if there is no damage that affects the secondary use); the material consumption is low. The thickness of the ceramic coating is generally between tens of microns and several millimeters. Moreover, the density of ceramic materials is relatively low, so the material consumption is small, but the added value is high; it is not limited by the size of the workpiece and the construction site. The sprayed products can be large or small, and the shape is not restricted; it can be constructed in the thermal spraying factory or on site.
[0003] However, the traditional preparation method of ceramic coating composite materials has the following disadvantages:
[0004] The density of traditional ceramic coating composite materials is not high, and the ceramic coating composite materials are easy to fall off after coating, which cannot meet people's usage needs. Summary of the invention
[0005] The purpose of the present invention is to provide a composite interface enhancement method for polymer materials and ceramic coatings to solve the problems mentioned in the above background technology that the density of traditional ceramic coating composite materials is not high, the ceramic coating composite materials are easy to fall off after coating, and cannot meet people's usage needs.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for enhancing the composite interface of a polymer material and a ceramic coating, comprising the following steps:
[0007] Step 1: Material selection: Select raw materials for preparing ceramic coating and then prepare ceramic preform;
[0008] Step 2: Surface treatment: using a surface sandblasting process to process the surface of the ceramic preform;
[0009] Step 3: First coating treatment: The reactant gas penetrates into the interior of the ceramic preform, chemical reactions occur and deposition is performed, and the formed ceramic coating is treated;
[0010] Step 4, preparing the first coating: mixing the prepared polymer material A raw materials and coating them on the ceramic substrate, and allowing them to stand to form the first coating;
[0011] Step 5, preparing the second coating: mixing the prepared polymer material B raw material and coating it on the first coating, and allowing it to stand to form the second coating;
[0012] Step 6: Second coating treatment: Perform acid-base neutralization and density treatment on the first coating and the second coating after coating.
[0013] As a preferred technical solution of the present invention, the preparation of the ceramic preform in the step one is specifically to layer the alumina fibers, zirconium oxide fibers, silicon carbide fibers and silicon nitride fibers in the direction of 0° / 0°, 0° / 45° or 0° / 90°, or to layer the alumina fiber cloth, zirconium oxide fiber cloth, silicon carbide fiber cloth and silicon nitride fiber cloth in the direction of 0° / 0°, 0° / 45° or 0° / 90°, and to prepare the fiber ceramic preform by needle punching.
[0014] As a preferred technical solution of the present invention, the surface sandblasting processing parameters in the surface treatment in step 2 are: sandblasting size 80 mesh, sandblasting pressure 0.7 MPa, sandblasting time 1 minute, sandblasting distance 15 cm, sandblasting angle 90° and ambient temperature is room temperature.
[0015] As a preferred technical solution of the present invention, the ceramic coating treatment in step three is specifically to form a blank by an impregnation process of a sinterable matrix ceramic raw material powder and continuous fibers, and then sinter them under pressure at high temperature to combine the matrix material and the fibers into a composite material.
[0016] As a preferred technical solution of the present invention, in step three, the reactant gas infiltrates into the interior of the ceramic preform by using trichloromethylsilane as the gas source, AR as the dilution gas, and bubbling H2 as the carrier gas to bring trichloromethylsilane into the reactor. The deposition temperature is about 1200°C, the total system pressure is 5kpa, and the molar ratio of H2 to trichloromethylsilane is 10:1.
[0017] As a preferred technical solution of the present invention, the raw materials of polymer material A in step 4 are specifically zirconium oxide, carboxyl prepolymer polymer, surfactant, hydroxyl radical scavenger and citric acid.
[0018] As a preferred technical solution of the present invention, the raw material of polymer material B in step 5 is specifically epoxy resin, polyester resin and polyetheretherketone.
[0019] As a preferred technical solution of the present invention, the acid-base neutralization in step six is specifically to wash the coating with a dilute sodium bicarbonate solution and apply it to the outside of the second coating to neutralize the surface acidity and strengthen the mechanical properties of the first coating and the second coating.
[0020] As a preferred technical solution of the present invention, the density treatment in step six is carried out by coating the outside of the second coating with a specific mixed powder combination, and the mixed powder is specifically a SiC inner layer slurry containing C powder, Si powder and HfSi2 or ZrSi2 modified components.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. By performing density treatment on the first coating and the second coating, the density of the coating sintering is significantly improved, and the phenomenon of ceramic coating composite materials falling off after coating is avoided, thus meeting people's use needs;
[0023] 2. By setting the first coating and the second coating, the coating of the first coating enhances the bending, compression and wear resistance of the ceramic coating, and the coating of the second coating enhances the corrosion resistance and high temperature resistance of the ceramic coating, and the prepared ceramic coating composite material has high practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a flow chart of the present invention;
[0025] Figure 2 It is the analysis diagram of different temperature states of the present invention;
[0026] Figure 3 This is a heating-quenching sample analysis diagram of the present invention;
[0027] Figure 4 This is a crystal plane analysis diagram of the ceramic coating composite material of the present invention;
[0028] Figure 5 This is a heating and quenching analysis diagram of the ceramic coating composite material of the present invention;
[0029] Figure 6 This is a heating and sintering analysis diagram of the ceramic coating composite material of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] See also Figure 1-6 The present invention provides a method for enhancing the composite interface of a polymer material and a ceramic coating, comprising the following steps:
[0032] Step 1: Material selection: Select raw materials for preparing ceramic coating and then prepare ceramic preform;
[0033] Step 2: Surface treatment: using a surface sandblasting process to process the surface of the ceramic preform;
[0034] Step 3: First coating treatment: The reactant gas penetrates into the interior of the ceramic preform, chemical reactions occur and deposition is performed, and the formed ceramic coating is treated;
[0035] Step 4, preparing the first coating: mixing the prepared polymer material A raw materials and coating them on the ceramic substrate, and allowing them to stand to form the first coating;
[0036] Step 5, preparing the second coating: mixing the prepared polymer material B raw material and coating it on the first coating, and allowing it to stand to form the second coating;
[0037] Step 6: Second coating treatment: Perform acid-base neutralization and density treatment on the first coating and the second coating after coating.
[0038] The preparation of the ceramic preform in step one is specifically to layer the alumina fibers, zirconium oxide fibers, silicon carbide fibers and silicon nitride fibers in the direction of 0° / 0°, 0° / 45° or 0° / 90°, or to layer the alumina fiber cloth, zirconium oxide fiber cloth, silicon carbide fiber cloth and silicon nitride fiber cloth in the direction of 0° / 0°, 0° / 45° or 0° / 90°, and to prepare the fiber ceramic preform by needle punching.
[0039] The surface sandblasting processing parameters in the surface treatment in step 2 are: sandblasting size 80 mesh, sandblasting pressure 0.7 MPa, sandblasting time 1 minute, sandblasting distance 15 cm, sandblasting angle 90° and ambient temperature is room temperature.
[0040] The ceramic coating treatment in step three is specifically to prepare a blank by impregnating the sinterable matrix ceramic raw material powder and the continuous fiber through an impregnation process, and then sintering under high temperature and pressure to combine the matrix material and the fiber into a composite material.
[0041] In step 3, the reactant gas penetrates into the interior of the ceramic preform by using trichloromethylsilane as the gas source and AR as the dilution gas. H2 is used as the carrier gas to bring trichloromethylsilane into the reactor in a bubbling manner. The deposition temperature is about 1200°C, the total system pressure is 5kpa, and the molar ratio of H2 to trichloromethylsilane is 10:1.
[0042] In step 4, the raw materials of polymer material A are specifically zirconium oxide, carboxyl prepolymer, surfactant, hydroxyl radical scavenger and citric acid.
[0043] In step 5, the raw materials of polymer material B are specifically epoxy resin, polyester resin and polyetheretherketone.
[0044] In step six, the acid-base neutralization is specifically to apply a dilute sodium bicarbonate solution to the washing coating on the outside of the second coating to neutralize the surface acidity and strengthen the mechanical properties of the first coating and the second coating.
[0045] In step six, the density treatment is carried out by coating the outer side of the second coating with a specific mixed powder combination, wherein the mixed powder is specifically a SiC inner layer slurry containing C powder, Si powder and HfSi2 or ZrSi2 modified components.
[0046] In the present invention, raw materials for preparing ceramic coatings are selected and then a ceramic preform is prepared, alumina fibers, zirconium oxide fibers, silicon carbide fibers and silicon nitride fibers are layered in the direction of 0° / 0°, 0° / 45° or 0° / 90°, or alumina fiber cloth, zirconium oxide fiber cloth, silicon carbide fiber cloth and silicon nitride fiber cloth are layered in the direction of 0° / 0°, 0° / 45° or 0° / 90°, and a fiber ceramic preform is prepared by a needle punching method; a surface sandblasting process is used to process the surface of the ceramic preform, and the surface sandblasting processing parameters are: sandblasting size 80 mesh, sandblasting pressure 0.7 MPa, sandblasting time 1 minute, sandblasting distance 15 cm, sandblasting angle 90° and ambient temperature of room temperature; the reactant gas penetrates into the interior of the ceramic preform, a chemical reaction occurs and deposition is performed, and the formed ceramic coating is treated The method comprises the following steps: using trichloromethylsilane as a gas source and AR as a diluent gas, and using H2 as a carrier gas to bring trichloromethylsilane into a reactor in a bubbling manner. The deposition temperature is about 1200°C, the total system pressure is 5kpa, and the molar ratio of H2 to trichloromethylsilane is 10:1; the prepared raw materials of polymer material A, zirconium oxide, carboxyl prepolymer, surfactant, hydroxyl radical scavenger and citric acid are mixed and coated on a ceramic substrate, and a first coating is formed after standing; the prepared raw materials of polymer material B, epoxy resin, polyester resin and polyetheretherketone are mixed and coated on the first coating, and a second coating is formed after standing; the first coating and the second coating after coating are subjected to acid-base neutralization and density treatment, and on the outside of the second coating, the mixed powder is specifically a SiC inner layer slurry containing C powder, Si powder and HfSi2 or ZrSi2 modified components.
[0047] In conjunction with the instruction manual Figure 2 As the WC grains grow, S2 WC / WC grain boundaries (GB) are formed between the nano-grains. At the same time, PB and GB, as diffusion and migration channels for atoms, promote the growth of grains and the evolution of phases. Therefore, compared with the cemented carbide prepared by traditional ceramic powder mixed sintering, it has a significantly improved coherent interface ratio. In the figure, (a) at room temperature, disordered amorphous structure; (b) at 550℃, ceramic crystals preferentially nucleate; (c) at 750℃, amorphous matrix, ceramic powder phase and a small amount of ceramic powder coexist; (d) at 800℃, crystallization is close to completion;
[0048] In conjunction with the instruction manual Figure 3 , Phase and composition analysis of samples heated and quenched at 800℃ and 900℃: (a) HRTEM image and phase analysis of amorphous powder heated at 800℃; (b) APT analysis of W, Co, and C element distribution in samples heated at 900℃; (c) Phase configuration of the local area of (b) determined by composition analysis;
[0049] In conjunction with the instruction manual Figure 4, the nucleation and growth of ceramic crystals from the amorphous matrix were observed on the typical characteristic crystal planes: (ab) the formation and growth characteristics of the (1-10) crystal planes of ceramic crystals, corresponding to the heating and quenching treatment conditions of 750℃, 800℃, and 850℃, respectively;
[0050] In conjunction with the instruction manual Figure 5 , grain boundary and phase boundary characteristics of the sample heated and quenched at 850℃: (a) coherent phase boundary of Co3W3C / WC and WC / hcp-Co; (b) coherent phase boundary of WC / fcc-Co;
[0051] In conjunction with the instruction manual Figure 6 In the fully densified nanocrystalline cemented carbide sintered at 1150℃, there are only WC and Co phases, and their coherent interfaces are as follows: (a) WC / fcc-Co phase boundary; (b) WC / hcp-Co phase boundary.
[0052] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for strengthening the composite interface of a polymer material and a ceramic coating, characterized in that: The following steps are involved: Step 1: Material selection: selecting raw materials for preparing ceramic coating and then preparing ceramic preform; Step 2: Surface treatment: using a surface sandblasting process to process the surface of the ceramic preform; Step 3: First coating treatment: The reactant gas penetrates into the interior of the ceramic preform, chemical reactions occur and deposition is performed, and the formed ceramic coating is treated; Step 4, preparing the first coating: mixing the prepared polymer material A raw materials and coating them on the ceramic substrate, and allowing them to stand to form the first coating; Step 5, preparing the second coating: mixing the prepared polymer material B raw material and coating it on the first coating, and forming the second coating after standing; Step 6: Second coating treatment: Perform acid-base neutralization and density treatment on the first coating and the second coating after coating.
2. The method for enhancing the composite interface of a polymer material and a ceramic coating according to claim 1, characterized in that: The preparation of the ceramic preform in step 1 is specifically to layer the alumina fibers, zirconium oxide fibers, silicon carbide fibers and silicon nitride fibers in the direction of 0° / 0°, 0° / 45° or 0° / 90°, or to layer the alumina fiber cloth, zirconium oxide fiber cloth, silicon carbide fiber cloth and silicon nitride fiber cloth in the direction of 0° / 0°, 0° / 45° or 0° / 90°, and to prepare the fiber ceramic preform by needle punching.
3. The method for enhancing the composite interface of a polymer material and a ceramic coating according to claim 1, characterized in that: The surface sandblasting processing parameters in the surface treatment in step 2 are: sandblasting size 80 mesh, sandblasting pressure 0.7 MPa, sandblasting time 1 minute, sandblasting distance 15 cm, sandblasting angle 90° and ambient temperature is room temperature.
4. The method for enhancing the composite interface of a polymer material and a ceramic coating according to claim 1, characterized in that: The ceramic coating treatment in step three is specifically to prepare a blank by impregnating the sinterable base ceramic raw material powder and the continuous fiber through an impregnation process, and then sintering under high temperature and pressure to combine the base material and the fiber into a composite material.
5. The method for enhancing the composite interface of a polymer material and a ceramic coating according to claim 1, characterized in that: In the step 3, the reactant gas penetrates into the interior of the ceramic preform by using trichloromethylsilane as the gas source, AR as the dilution gas, and using H2 as the carrier gas to bring trichloromethylsilane into the reaction furnace in a bubbling manner. The deposition temperature is about 1200° C., the total system pressure is 5 kPa, and the molar ratio of H2 to trichloromethylsilane is 10:
1.
6. The method for enhancing the composite interface of a polymer material and a ceramic coating according to claim 1, characterized in that: The raw materials of polymer material A in step 4 are specifically zirconium oxide, carboxyl prepolymer, surfactant, hydroxyl radical scavenger and citric acid.
7. The method for enhancing the composite interface of a polymer material and a ceramic coating according to claim 1, characterized in that: The raw materials of polymer material B in step 5 are specifically epoxy resin, polyester resin and polyetheretherketone.
8. The method for enhancing the composite interface of a polymer material and a ceramic coating according to claim 1, characterized in that: The acid-base neutralization in step six is specifically to apply a diluted sodium bicarbonate solution to the washing coating on the outside of the second coating to neutralize the surface acidity and strengthen the mechanical properties of the first coating and the second coating.
9. The method for enhancing the composite interface of a polymer material and a ceramic coating according to claim 1, characterized in that: The density treatment in step six is performed by coating the outer side of the second coating with a specific mixed powder combination, wherein the mixed powder is specifically a SiC inner layer slurry containing C powder, Si powder and HfSi2 or ZrSi2 modified components.
